Da liberdade transcendental à liberdade prática : a transição da crítica da razão pura para a crítica da razão prática - Orben, Douglas João (2014)
With the purpose to present the philosophic transition from theoretical freedom to practical freedom in Kant, this text is centered in Critique of pure reason (Transcedental Dialectic, above all) and in Critique of practical reason. Trying to overcome a reading that reduces the purposes of the first Critique to the delimitation of the possible knowledge, it s an intention to demonstrate the transcendental naturality such as the systematic relevance that the metaphysic ideas assume already in theoretical philosophy. Then, the discussion focus the concept of transcendental freedom, that presents as not contradictory for the speculative reason, what can be thought without contradicting the rigorous natural laws. Pacifying the conflict between spontaneous causality (free) and the phenomenal causality (determinate), so the conditions to the edification in practical circuit, by means of the possibility of an unconditioned dominion, secured by the theoretical freedom are visualized. In this sense, in spite of the self-sufficiency of the Kant s practical philosophy, it isn t indifferent about the results achieved by the theoretical reason, because it s through these effects that the moral enterprise receives investigative legitimacy. On the other hand, so far as the moral law reality presents as a factum of the reason, besides the evidence of the practical range, the own negative freedom concept assumes a positive reality. If the practical reality of the moral law is demonstrated, so the objective reality of the freedom is equally confirmed, because the freedom is the basic condition for morality. Then, the transition from the first to the second Critique reveals the philosophic importance of the freedom concept, as to satisfy the speculative reason as to edify the project of the practical reason, taking care with the systematic linkage of both dominions.